Analysis of Extreme Phenotype Bulk Copy Number Variation (XP-CNV) Identified the Association of rp1 with Resistance to Goss's Wilt of Maize - Hu, Ying; Ren, Jie; Peng, Zhao; Umana, Arnoldo A.; Le, Ha; Danilova, Tatiana; Fu, Junjie; Wang, Haiyan; Robertson, Alison; Hulbert, Scot H.; White, Frank F.; Liu, Sanzhen (Frontiers in Plant Science, 2018)
Goss’s wilt (GW) of maize is caused by the Gram-positive bacterium Clavibacter michiganensis subsp. nebraskensis (Cmn) and has spread in recent years throughout the Great Plains, posing a threat to production. The genetic basis of plant resistance is unknown. Here, a simple method for quantifying disease symptoms was developed and used to select cohorts of highly resistant and highly susceptible lines known as extreme phenotypes (XP). Copy number variation (CNV) analyses using whole genome sequences of bulked XP revealed 141 genes containing copy number variation between the two XP groups. The CNV genes include the previously identified common rust resistant locus rp1. Multiple Rp1 accessions with distinct rp1 haplotypes in an otherwise susceptible accession exhibited hypersensitive responses upon inoculation. GW provides an excellent system for the genetic dissection of a disease, which is caused one of several closely related subspecies of C. michiganesis. Further work will facilitate breeding strategies to control GW and provide needed insight into the important related diseases bacterial canker of tomato and bacterial ring rot of potato.